Asymmetry in above‐ and belowground productivity responses to N addition in a semi‐arid temperate steppe - Wang, Jing; Gao, Yingzhi; Zhang, Yunhai; Yang, Junjie; Smith, Melinda D.; Knapp, Alan K.; Eissenstat, David M.; Han, Xingguo (Global change biology, 2019)
Nitrogen (N) enrichment often increases aboveground net primary productivity (ANPP) of the ecosystem, but it is unclear if belowground net primary productivity (BNPP) track responses of ANPP. Moreover, the frequency of N inputs may affect primary productivity but is rarely studied. To assess the response patterns of above‐ and belowground productivity to rates of N addition under different addition frequencies, we manipulated the rate (0–50 g N m−2 year−1) and frequency (twice vs. monthly additions per year) of NH4NO3 inputs for six consecutive years in a temperate grassland in northern China and measured ANPP and BNPP from 2012 to 2014. In the low range of N addition rates, BNPP showed the greatest negative response and ANPP showed the greatest positive responses with increases in N addition (<10 g N m−2 year−1). As N addition increased beyond 10 g N m−2 year−1, increases in ANPP dampened and decreases in BNPP ceased altogether. The response pattern of net primary productivity (combined above‐ and belowground; NPP) corresponded more closely to ANPP than to BNPP. The N effects on BNPP and BNPP/NPP (fBNPP) were not dependent on N addition frequency in the range of N additions typically associated with N deposition. BNPP was more sensitive to N addition frequency than ANPP, especially at low rates of N addition. Our findings provide new insights into how plants regulate carbon allocation to different organs with increasing N rates and changing addition frequencies. These root response patterns, if incorporated into Earth system models, may improve the predictive power of C dynamics in dryland ecosystems in the face of global atmospheric N deposition. We manipulated the rate and frequency of nitrogen inputs for six consecutive years in a temperate grassland in northern China and measured aboveground net primary productivity (ANPP) and belowground net primary productivity (BNPP) from 2012 to 2014. We found that in the low range of N addition rates, BNPP showed the greatest negative response and ANPP showed the greatest positive responses with increases in N addition. As N addition increased beyond 10 g N m−2 year−1, increases in ANPP dampened and decreases in BNPP ceased altogether.